Researching social problems - Marvasti, Amir B. 1966-; Treviño, A. Javier 1958- (London Routledge, Taylor & Francis Group, 2020)
"This book covers a wide range of contemporary methods for researching social problems and connects these approaches to the broader substance and theories of social problems. Expository and discursive in approach, chapters follow a uniform structure, with each offering research examples and a broad description of the related method and its theoretical context, together with a 'how-to' guide for applying that method using substantive examples from the field of social problems. For every method explored, there is a research example that fully reviews and illustrates the application of the particular method, before giving a full assessment of the method's strengths and weaknesses and latest developments. With chapters exploring survey interviews, in-depth interviews, narrative inquiry, institutional ethnography, participatory action research, auto-ethnography, social network research, experimental research, visual research methods, and research ethics, Researching Social Problems will appeal to scholars and students of sociology and politics working in the fields of research methods and social problems"-- |c Provided by publisher.
Includes bibliographical references and index.
Keywords: Social problems -- Research; Social sciences -- Research